Efeito da aplicação do microjateamento de óxido de alumínio e discos de óxido de alumínio na resistência adesiva de braquetes metálicos recolados em esmalte previamente erodido - Leão, Luciana de Vasconcelos (2017)
Dental erosion is a result of the demineralization of enamel surface by the action of acids that soften it, and it may affect bracket adhesion to enamel. This research aimed to assess the effect of the application of aluminum oxide sandblasting and aluminum oxide discs on bond strength of metal brackets rebonded on artificially eroded enamel. Fifty-four crowns of bovine incisors were divided into group functions: Control (artificial saliva), Ox Al (aluminum oxide sandblasting), and SL (aluminum oxide discs Sof-Lex Pop On, 3M ESPE). The crowns were fixed in PVC tubes and enamel surface was flattened with carborundum discs (#320, 600, and 1200 Al2O3 discs; Buehler, Lake Bluff, IL, USA) in metallographic polisher (APL4, Arotec). Knoop microhardness was assessed for the standardization of enamel surfaces (HMV-2000; Shimadzu Corporation, Tokyo, Japan). Next, Ox Al and SL teeth were subjected to the erosive action, submerged in Coca-Cola™ for 1 minute, 3x a day for 7 days. Kirium metal brackets, specific for upper right central incisors, slot 022, Roth prescription (3M/Abzil, São José do Rio Preto, São Paulo, Brazil) were bonded on the buccal aspect of teeth. Shear strength was measured with a universal testing machine EMIC (DL200, EMIC, São José dos Pinhais, Paraná, Brazil) at speed of 0.5 mm/min. The Adhesive Remnant Index (ARI) was performed in samples after shear through a magnifying glass (10x). Kolmogorov-Smirnov, Levene, and homoscedasticity tests were used, as well as ANOVA, for the assessment of microhardness and shear strength. The three groups presented no significant differences for microhardness and shear, but the control group had the highest microhardness mean. There were no statistically significant differences among the three groups for shear bond strength (p=0.163). However, the Ox Al group showed higher values for bond strength. The assessment of ARI of groups showed statistically significant difference when comparing the Control group with Ox Al and SL groups. The ARI values showed the prevalence of ARI 3 (50%) for the control group, followed by ARI 4 (22%) and 5 (22%). For Ox Al and SL, ARI 1 and 2 prevailed. The use of aluminum oxide sandblasting and aluminum oxide discs did not increase bond strength of brackets when they were bonded on artificially eroded enamel. The Adhesive Remnant Index indicated that eroded teeth present higher resin adhesion to enamel.